2021
DOI: 10.1111/ele.13759
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent effects of niche specialisation: The disconnect between individual and species ranges

Abstract: One of the most general expectations of species range dynamics is that widespread species tend to have broader niches. However, it remains unclear how this relationship is expressed at different levels of biological organisation, which involve potentially distinctive processes operating at different spatial and temporal scales. Here, we show that range sizes of terrestrial non‐volant mammals at the individual and species level show contrasting relationships with two ecological niche dimensions: diet and habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 140 publications
(177 reference statements)
2
16
0
Order By: Relevance
“…A brain that requires less energy would therefore allow carnivorans to settle more easily and sustainably in new environments. Our hypothesis also echoes a recent study which demonstrates that home range size in terrestrial mammals is the result of a trade-off between the ecological specialization of a species and its ability to move, while the geographic distribution is linked to the ability of a species to resist to various environments [97] . Like Huang et al [97] , our result re ects a potential impact of natural selection at two different evolutionary scales: the use of the surrounding environnement by individuals, and the dispersal of species within different habitats and localities.…”
Section: Environmental Factors May Have Played An Important Role In the Evolution Of Carnivoran Brain Sizesupporting
confidence: 88%
See 1 more Smart Citation
“…A brain that requires less energy would therefore allow carnivorans to settle more easily and sustainably in new environments. Our hypothesis also echoes a recent study which demonstrates that home range size in terrestrial mammals is the result of a trade-off between the ecological specialization of a species and its ability to move, while the geographic distribution is linked to the ability of a species to resist to various environments [97] . Like Huang et al [97] , our result re ects a potential impact of natural selection at two different evolutionary scales: the use of the surrounding environnement by individuals, and the dispersal of species within different habitats and localities.…”
Section: Environmental Factors May Have Played An Important Role In the Evolution Of Carnivoran Brain Sizesupporting
confidence: 88%
“…This scenario is also supported by studies which show that the risk of extinction is higher in mammals with relatively larger brains [98] . Finally, it is possible that populations with a large geographic distribution may also display higher intra-speci c variability of their EQ [97] . Our analyses do not allow us to speci cally test this phenomenon, but we acknowledge the importance of investigating intra-speci c brain size differences in the future to better understand the evolution of encephalization at different scales and test the strength of our hypothesis.…”
Section: Environmental Factors May Have Played An Important Role In the Evolution Of Carnivoran Brain Sizementioning
confidence: 99%
“…These patterns are particularly true for small-sized mammals, although results remained unchanged when including all species. We also showed that, as predicted by theoretical work [8,20,22,53,54], the variance in ranges sometimes assigned to body mass [9] was accounted for by metabolic traits, when both mass and metabolic traits are considered explicitly.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, while competition is an important driver of species distributions at the local scale, it presumably has a limited effect at the global scale ( [4], but see [5]). That has led to fine-and large-scale ecological phenomena being scrutinized either separately [6][7][8] or, when considered together, using disparate explanatory variables with loose connections [9]. A clear example is the question of what underpins organisms' distribution ranges ( [4], but see [10]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation